Kazimiera Iłłakowiczówna mniej więcej znana - Marzec, Lucyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article is the analysis of the place of Kazimiera Iłłakowiczówna in contemporary literary discourse. The author of the article claims – using Pierre Bayard’s theory – that the poetess is known “more or less”: she is remembered as someone who got prizes and recognition but at the same time she is impossible to read nowadays. There is political ambiguity and antiquity in her texts that keep her in the past. Marzec points at four areas of literary studies, where Iłłakowiczówna is still present: 1. Poetics: Iłłakowiczówna uses an original and unusual type of the Polish tonic verse. The author of this article analyses it using tools of psychoanalysis. 2. Religious discourse: Iłłakowicz.wna is interpreted as the author of religious poetry but Marzec argues with such interpretations. 3. Post-dependence studies: Iłłakowiczówna has not been analysed in terms of post-dependence studies yet but she is mentioned in the Polish borderlines discourse. 4. Feminist literary criticism: Iłłakowiczówna used to be studied as the author of androgynous poetry, but Marzec points out other motifs such as miscarriage, infanticide or problems of the new woman, like work at government institution, contestation of vitalism and bureaucracy. The aimof this article is to show that writing of Kazimiera Iłłakowiczówna needs to be read in terms of the history of literature which is devoid of evaluation and judging. Such analysis means going back in terms of modern literary studies which have undergone multiple turns that changed the tools accessible to contemporary critics.